Bung Karno menggugat! : dari Marhaen, CIA, pembantaian Massal'65 hingga G 30 S - Wardaya, Baskara T. (Tulus) (Yogyakarta : Galangpress, 2006)
Analysis of Soekarno's ideas and political decisions from the start of his political career; describes his position and attitude towards colonialism and US involvement in Indonesian domestic affairds, includes a comparison between his and Suharto's style of leadership
Daftar pustaka: p. 275-279 and index
Keywords: Soekarno, -- 1901-1970; Indonesia -- Political parties -- History and criticism; Indonesia -- Politics and government -- History